Pelaksanaan Eksekusi Benda Jaminan Kredit yang Tidak Mencukupi untuk Pelunasan Utang di Koperasi Guna Arta Karangasem - I Gede Agus Wira Sanjaya; I Nyoman Putu Budiartha; Desak Gde Dwi Arini (Jurnal Konstruksi Hukum, 2021)
This study aims to determine the credit agreement or business loan between the customer and the cooperative and to find out the settlement in the event of a dispute in the credit agreement between the customer and the cooperative. This study uses empirical research methods where the method is based on positive law and norms. The results showed that the agreement made between the cooperative and the customer is based on the agreement of the parties who are ready to carry out their obligations and get rights. The obligation of the cooperative to provide loan funds to customers is the right of the cooperative to benefit from interest from customer loan funds. The obligation of the customer to pay the loan on time that has been agreed upon because he has lent funds, the right of the customer to get a loan for the customer's needs according to the agreement of the parties. Then, the agreement of the parties is not a guarantee that there will be no default, the importance of a legal attorney in an agreement makes it easier to resolve problems between the parties. Legal attorneys provide options for ending the case through the court (litigation) and settlement in a family way (non-litigation). Most parties use the non-litigation route because they want everything to be done quickly but at low cost. If the non-litigation solution does not find a middle ground, the case will proceed to court. Judge's rule applies to parties in litigation from the time until the costs incurred. Those who lost are willing to be asked for compensation for their actions.